Unsur Biophilic pada Desain Amphitheater Di Kawasan Ekowisata Kelompok Tani Manglayang Bandung - Mi'raj, Ceppy Rangga Naufal; Saryanto, Saryanto (Waca Cipta Ruang, 2024)
The Manglayang Bandung Farmers Group Ecotourism Area encompasses a large expanse of land that has yet to be fully utilised. This area is intended to become a destination for visitors, in line with its ecotourism tagline. To achieve this vision, the development of a new structure is necessary. As part of the planning, an amphitheater design has been proposed, based on the expected behaviours of future users and incorporating biophilic elements to create a refreshing atmosphere for visitors. The amphitheater design integrates biophilic principles to foster a connection between nature and the activities taking place within the facility. This approach focuses on the use of natural materials, vegetation, scenic views, natural lighting, and sensory stimulation to enhance visitors' psychological perception of nature. The design process follows a qualitative methodology, using a design thinking framework as its foundation. The outcome is anticipated to provide visitors with new and enriching experiences in the amphitheater. Keywords: Amphitheater, Biophilic, Designing, Ecotourism